EFFICACY OF EUTECTIC MIXTURE OF LOCAL ANESTHETICS VS LIDOCAINE SPRAY ON PAIN DURING ARTERIOVENOUS FISTULA CANNULATION IN HEMODIALYSIS PATIENTS - Masih, Shelly; Sharma, Kapil; Rani, Sunita (American Research Journal of Nursing and Health Sciences (ARJNHS), 2023)
Arteriovenous fistula cannulation is a painful procedure in Hemodialysis patients. The study aimed to compare the efficacy of eutectic mixture of local anesthetics and Lidocaine spray on pain during arteriovenous fistula (AVF) cannulation in 30 patients visiting the dialysis unit of DMC & Hospital, Ludhiana, Punjab. Pain was assessed using a Numerical Pain Rating scale. Descriptive and inferential statistics were used to analyze the data. The study found that the eutectic mixture of local anesthetics was more effective than Lidocaine spray in reducing pain during AVF cannulation. The results can help improve the dialysis acceptance and life quality of Hemodialysis patients.